2011
DOI: 10.1093/ejcts/ezr049
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of monocyte chemoattractant protein-1 expression by ischaemic preconditioning in a lung autotransplant model

Abstract: In this model, LIRI induced the expression of MCP-1 and the proinflammatory proteins TNF-α and IL-1 in control lungs. IP significantly reduced the expression of these chemokines and cytokines. These features may explain the reduction of oxidative stress observed with IP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…2,20,21 Besides reactive oxygen and nitrogen species, massive production of pro-inflammatory cytokines 1,4,5 and reduced expression of growth factors 6 plays a central role in mediating inflammation in ARDS. 1,5 For instance, IL-1β, a potent pro-inflammatory cytokine, is centrally involved in the mechanism of lung injury and regulates microvascular endothelial permeability. 47 Here, we observed that Cr supplementation reduced I/R-induced high plasma levels of IL-1β, which was followed by reduced pulmonary perivascular edema.…”
Section: Figurementioning
confidence: 99%
“…2,20,21 Besides reactive oxygen and nitrogen species, massive production of pro-inflammatory cytokines 1,4,5 and reduced expression of growth factors 6 plays a central role in mediating inflammation in ARDS. 1,5 For instance, IL-1β, a potent pro-inflammatory cytokine, is centrally involved in the mechanism of lung injury and regulates microvascular endothelial permeability. 47 Here, we observed that Cr supplementation reduced I/R-induced high plasma levels of IL-1β, which was followed by reduced pulmonary perivascular edema.…”
Section: Figurementioning
confidence: 99%
“…Ischaemic conditioning has a myriad of effects on the inflammatory response to IR, it reduces the expression of inflammatory cytokines such as TNF-α, IL1b, IL6, CCL2; reduces leucocyte recruitment and extravasation by downregulating ICAM [ 107 , 111 , 113 ]. The reduction in neutrophil chemotaxis and activity also reduces of the production of ROS, as seen by a reduction in MDA and lipid hydroperoxides (LPO) production [ 27 ]. In addition, ischaemic conditioning also reduces mediators of apoptosis, including BAX, Caspase, cytochrome C and Fas ligand [ 108 , 112 ].…”
Section: Novel Therapies For Ischaemia–reperfusion Injurymentioning
confidence: 99%
“…IRI is often characterised by rapid accumulation of ROS soon after reperfusion, with increased activities of ROSgenerating enzymes such as NADPH oxidase, xanthine oxidase and myeloperoxidase [8,17,22,23]. Reduction in anti-oxidative capacity [15,24] and the occurrence of oxidative stress [24][25][26][27] are also observed. NADPH oxidase activity seems to play a significant role in the pathophysiology of IRI, as NADPH oxidase knockout animal demonstrates significantly blunted oxidative stress and inflammatory response to IRI.…”
Section: Oxidative and Nitrosative Stressmentioning
confidence: 99%
“…When the antioxidant defense capabilities of the lung, for example, are overburdened and unable to cope with the increase in ROS, deviations in cellular metabolic function and redox signaling occur. Oxidative stress due to ROS causes proin ammatory cytokine release and enhanced transcription of numerous genes resulting in in ammation, cell injury, and neutrophil recruitment and activation in the lung after ischemic reperfusion (IR) and reoxygenation [40][41][42][43][44][45]. Cells undergoing reperfusion and reoxygenation following hypoxia produce super oxide radical [46].…”
Section: Determinants Of In Ammatory Responsivitymentioning
confidence: 99%